Iklan TV Menggunakan Celebrity Endorse terhadap Sikap Konsumen serta Dampaknya pada Niat Beli Produk Honda - Alwi Noer Muhamad; Asep M. Ramdan; Kokom Komariah (Journal of Management and Bussines (JOMB), 2022)
This study aimed to analyze the trends of celebrity and consumer support for the intention to buy consumers on Honda products at PT. Happy Lestari Mandiri City Sukabumi. The method used was simple random sampling by distributing 188 questionnaires to consumers. The data analysis technique used is the analysis path. In this method, simultaneous and partial methods are used. As a step in testing the partial influence are as follows coefficient testing, coefficient testing, coefficient determination, calculating the influence of other variables and simple linear regression. While the calculation of influence simultaneously the steps are as follows double counting, determination coefficient, other influence variables and multiple linear regression, after that calculate directly and indirectly and finally use the test simultaneously (F test) and test using partial (T test) . Keywords: celebrity endorse, consumer attitude towards advertising, consumer purchase intention